Aplikasi Sistem Informasi Geografi (SIG) untuk Penyusunan Arahan Pengembangan Perumahan di Kabupaten Sleman - Prasetyo, Fahmi Nur, Dr. Kuswaji Dwi Priyono, M. Si, Agus Anggoro Sigit, S.Si., M.Sc (2015)
The objective of this research was to identify the potency and the area availability to develop housing, organize Housing Development Information System in Sleman Regency and make recommendation about the selection of housing development location in Sleman Regency. The method used in this research was secondary data analysis. The analysis technique used was descriptive analysis by making thematic map (Map of Housing Development Location in Sleman Regency) starting from the overlay process of basic maps (Administrative Map, Land Use map, Unsafe Disaster Map, Layout Area Plan Map and Sleman Regency Area Status Map). The map of Sleman Regency Housing Development Location and also the supporting data were arranged in geography information system. The main result of this research was the Map of Sleman Regency Housing Development Location which contained spatial information about areas recommended to develop housing, areas recommended to develop housing limitedly, main recommended areas to develop housing and also the spread of built area around recommended area of housing development. That map was arranged Sleman Regency Housing Development Information System with the map and another supporting data. It could be concluded from the research that the information system of housing development was one of the informative management area means which was needed in coordination of land matters, land matters solution and the building plan of land matters.